Factors Controlling Dead Wood Decomposition in an Old-Growth Temperate Forest in Central Europe - Jomura, Mayuko; Yoshida, Riki; Michalčíková, Lenka; Tláskal, Vojtěch; Baldrian, Petr (Journal of fungi (Basel, Switzerland), 2022)
Dead wood represents an important pool of carbon and nitrogen in forest ecosystems. This source of soil organic matter has diverse ecosystem functions that include, among others, carbon and nitrogen cycling. However, information is limited on how deadwood properties such as chemical composition, decomposer abundance, community composition, and age correlate and affect decomposition rate. Here, we targeted coarse dead wood of beech, spruce, and fir, namely snags and tree trunks (logs) in an old-growth temperate forest in central Europe; measured their decomposition rate as CO2 production in situ; and analyzed their relationships with other measured variables. Respiration rate of dead wood showed strong positive correlation with acid phosphatase activity and negative correlation with lignin content. Fungal biomass (ergosterol content) and moisture content were additional predictors. Our results indicate that dead wood traits, including tree species, age, and position (downed/standing), affected dead wood chemical properties, microbial biomass, moisture condition, and enzyme activity through changes in fungal communities and ultimately influenced the decomposition rate of dead wood.
Keywords: chemical properties; fungal biomass; respiration; extracellular enzymes; structural equation modeling; fungal community